ESP in Practice: A Literature Review of Challenges Faced by Teachers and Learners - Dilla Sintia; Indra Perdana; Elanneri Karani (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
ESP means teaching of English for vocational or professional purposes. ESP concentrates on giving students the language skills required for efficient communication in specialized fields. This literature review investigates the major instructional challenges faced by educators and learners in English for Specific Purposes (ESP), particularly those related to content knowledge gaps, lack of authentic materials, curriculum alignment, and technological limitations in specialized academic and vocational settings. This review identifies five major challenges: (1) a gap in subject-matter knowledge among ESP instructors, (2) a lack of authentic, field-specific learning materials, (3) learners’ struggles with technical language and genre-specific discourse, (4) inadequate needs analysis and curriculum alignment, and (5) technological limitations that hinder digital integration. The findings suggest that many ESP programs fall short due to a lack of institutional support, insufficient teacher training, and weak collaboration between language educators and content experts. To address these challenges, the review recommends interdisciplinary cooperation, the development of contextually relevant resources, continuous needs assessment, and strategic use of educational technology. These steps are essential for improving the relevance and effectiveness of ESP instruction in diverse educational and professional settings.